Colloidal particle aggregation: mechanism of assembly studied via constructal theory modeling - Bukosky, Scott C.; Dev, Sukrith; Allen, Monica S.; Allen, Jeffery W. (Beilstein Journal of Nanotechnology, 2021)
The assembly of colloidal particles into ordered structures is of great importance to a variety of nanoscale applications where the precise control and placement of particles is essential. A fundamental understanding of this assembly mechanism is necessary to not only predict, but also to tune the desired properties of a given system. Here, we use constructal theory to develop a theoretical model to explain this mechanism with respect to van der Waals and double layer interactions. Preliminary results show that the particle aggregation behavior depends on the initial lattice configuration and solvent properties. Ultimately, our model provides the first constructal framework for predicting the self-assembly of particles and could be expanded upon to fit a range of colloidal systems.
Keywords: colloids; constructal law; DLVO theory; interparticle interactions; nanomaterials; self-assembly; tunable systems